Non-Linear Mixed Logit and the Characterization of Individual Heterogeneity - Steffen Andersen; Glenn W. Harrison; Arne Risa Hole; Elisabet E. Rutström (Copenhagen Business School (CBS), Department of Economics, 2009)
Experimental data exhibit considerable individual heterogeneity. We review the econometric methods employed to characterize that heterogeneity. We pay particular attention to the trade-off between collecting and allowing for observable characteristics, such as the familiar demographics, and the use of statistical methods to allow for unobserved individual heterogeneity. We demonstrate that these tools are complementary.
hdl:10398/7802
Keywords: C01; J11; 330; econometrics; demography